A novel system for forensic SNP analysis through PCR–ligase detection reaction. (December 2015) - He, W.; Mao, J.; Feng, T.; Wang, L.; Li, Z.; Zu, W.; Liang, W.; Zhang, L.
Abstract: With the advantages of lower mutation rates and improved analysis of the degraded or aged samples, single nucleotide polymorphism (SNP) markers has been considered as supplementary to the STRs. Consequently, a robust, simple and cost effective technique for SNP typing is essential to analyze a large number of SNPs. Ligase detection reaction (LDR) could detect a SNP on CE platform through the ability of DNA ligase which can seal the nick junction formed by oligonucleotides hybridized to the flank region of target SNP. Here we purposed a prestudy to set up a 8 Y-SNPs (M9, M74, M35, M95, M110, M89, M13, M20) multiplex panel for forensic application through PCR–ligase detection reaction (LDR) system. Primers of 8 loci were designed for multiplexed PCR. According to the sequence around the SNP site, three LDR probes were designed for each SNP including one common fluorescent labeled probe and two allele specific probes different in size with mismatching bases at the 3' end. PCR–LDR products were profiled through ABI3130 Genetic Analyzer. A set of 8 Y-SNP could be profiled through two multiplexed PCR and two multiplexed LDR. Even though the number of markers in the current system is limited, when fully developed, it can easily be multiplied more SNPs and yield a greater power of discrimination. Our study indicated that the PCR-LDR could provide a robust, simple and cost effective multiplexed SNP typing method for forensic cases in the future.